2015
DOI: 10.7150/ijbs.12044
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Highly Palatable Food on the Behavioral and Neural Adversities induced by Early Life Stress Experience in Female Rats

Abstract: This study examined the effects of highly palatable food during adolescence on the psycho-emotional and neural disturbances caused by early life stress experience in female rats. Female Sprague-Dawley pups were separated from dam for 3 h daily during the first two weeks of birth (MS) or left undisturbed (NH). Half of MS females received free access to chocolate cookies in addition to ad libitum chow from postnatal day 28. Pups were subjected to the behavioral tests during young adulthood. The plasma corticoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The clinical literature has shown that individuals with a history of childhood abuse can use emotional eating as a coping strategy to deal with current symptoms of depression and/or emotional dysregulation (Michopoulos et al, 2015). Likewise, the rodent literature has demonstrated that consumption of 'comfort foods' ameliorates some of the stress and emotional dysregulation (Kim et al, 2015;Lee, Kim, & Jahng, 2014b;Maniam & Morris, 2010;Nelson et al, 2009). Thus, the increased preference for cafeteria diet induced by early-life adversity might be an attempt to ameliorate some of the emotional dysregulation experienced by adversely reared animals (Raineki et al, 2012(Raineki et al, , 2015Walker et al, 2017).…”
Section: Impact Of Early-life Adversity and Cafeteria Diet On Energy mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical literature has shown that individuals with a history of childhood abuse can use emotional eating as a coping strategy to deal with current symptoms of depression and/or emotional dysregulation (Michopoulos et al, 2015). Likewise, the rodent literature has demonstrated that consumption of 'comfort foods' ameliorates some of the stress and emotional dysregulation (Kim et al, 2015;Lee, Kim, & Jahng, 2014b;Maniam & Morris, 2010;Nelson et al, 2009). Thus, the increased preference for cafeteria diet induced by early-life adversity might be an attempt to ameliorate some of the emotional dysregulation experienced by adversely reared animals (Raineki et al, 2012(Raineki et al, , 2015Walker et al, 2017).…”
Section: Impact Of Early-life Adversity and Cafeteria Diet On Energy mentioning
confidence: 99%
“…In (d), the black arrow indicates hepatocytes with microvesicular steatosis and the white arrow indicates hepatocytes with macrovesicular steatosis TA B L E 2 Hepatic steatosis (expressed as a percentage) following early-life adversity and cafeteria diet early-life adversity(Kim et al, 2015;Lee, Kim, & Jahng, 2014b;Maniam & Morris, 2010;Nelson et al, 2009). In (d), the black arrow indicates hepatocytes with microvesicular steatosis and the white arrow indicates hepatocytes with macrovesicular steatosis TA B L E 2 Hepatic steatosis (expressed as a percentage) following early-life adversity and cafeteria diet early-life adversity(Kim et al, 2015;Lee, Kim, & Jahng, 2014b;Maniam & Morris, 2010;Nelson et al, 2009).…”
mentioning
confidence: 99%
“…Similar stress-buffering characteristics of a high fat diet ( ad lib access) have been observed in adult rats exposed to prolonged maternal separation. In these studies, the high-fat diet normalized anxiety-like behavior in the elevated plus maze, open field test and light-dark box test, in maternally separated rats when tested in late adulthood (Maniam and Morris, 2010a , b ; Marcolin Mde et al, 2012 ; Kim et al, 2015 ). Though in our study the stressor was administered during juvenility and access to the palatable diet was limited, our results further support the possibility that a high fat diet can mitigate the persisting effects of stressor exposure during key developmental periods.…”
Section: Resultsmentioning
confidence: 99%
“…In this vein, ingestion of palatable food amid a stressful environment decreases plasma adrenocorticotropic hormone (ACTH) and corticosterone levels, and reduces corticotrophin stimulating hormone (CRH) mRNA expression at the paraventricular nucleus of the hypothalamus, indicating that a palatable diet may dampen hypothalamic-pituitary-adrenal (HPA) axis response to stress (Dallman et al, 2003 ; Pecoraro et al, 2004 ; Ulrich-Lai et al, 2007 ; Christiansen et al, 2011 ; Zeeni et al, 2012 ). For instance, access to a high fat cafeteria diet or chocolate cookies was reported to reverse the anxiogenic and depressive traits induced by early-life stressors and normalize CRH expression and basal corticosterone levels in adulthood (Maniam and Morris, 2010a ; Marcolin Mde et al, 2012 ; Krolow et al, 2013 ; Machado et al, 2013 ; Kim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…37 On the other hand, other findings suggest that the consumption of palatable diet reduces anxiety-like behaviors in rodents independent of the neonatal group. 10,23,26,[38][39][40] A classic study demonstrates that even short-term exposure (7 days) to a high-fat diet decreases anxiety parameters in male adult rats evaluated in the high-labyrinth test. 41 It is possible that more subtle aspects of the diet composition, such as the polyunsaturated fatty acids content, may be involved in these differences.…”
mentioning
confidence: 99%